The breeding of buffalo in Hungary - Barna, Brigitta; Holló, Gabriella (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
In this study the authors analysed the management of buffalo breeding, the keeping and feeding conditions, depending on the purpose of breeding: milk or meat production traits. In the farms, the animals are on the pasture in the most part of the year and most of them are keeping in outdoors without building in the winter, too. The buffalo is well adapted to extreme weather conditions (dry, hot summer), and especially suitable for use in wet marshy areas. In winter supplementary feed (alfalfa hay, grass hay, oat hulls) is required to provide for the animals. The length of productive life of buffalo is 10–15 years; the main culling causes can be tracked back to reproductive and locomotion problems. The behaviour and temperament of buffalos affect the habitat and keeping conditions, too. The wallowing is a typical behaviour form of buffalo in the wet marshy areas. The temperament of dairy herd seems to be calmer than that of non-dairy animals. The milking speed of the buffalo cows and the amount of the milk are lower than the cattle. No significant physical behaviour response of buffalo to machine milking was detected, but the presence of calves affect the milk let down. Due to the higher fat content, the dry matter content of buffalo milk is higher than that of the cow milk. The casein content of buffalo milk is similar to the concentrate milk producing cows. The average dressing percentage of buffalo heifers are lower than cattle, because of the thicker skin and bigger weight of visceral organs of buffalo. The percentage of lean meat corresponds to the lean meat percentage of dairy cattle. The buffalo has higher bone content (21%) than cattle. The fat content is 10%, while the content of tendon is less than 1%. The average intramuscular fat content of longissimus muscle is 2.8%.
Keywords: buffalo breeding; buffalo milk; buffalo meat